NITRIC OXIDE AND ABSOLUTE NEUTROPHIL COUNT CORRELATION WITH OUTCOME IN ACUTE ISCHEMIC STROKE PATIENTS - Rina Harlianti; Yuneldi Anwar; Ratna Akbari Ganie (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
Nitric Oxide (NO) has a dual role as neuroprotector and neurotoxic in the pathophysiology of brain ischemia. Patients with acute ischemic stroke often have increased leukocyte count when admitted to hospital. Patients with acute ischemic stroke with high leukocyte count often have poor clinical outcomes. This study aims to determine the correlation of Nitric Oxide (NO) levels and Absolute Neutrophil Count with patients with outcome of acute ischemic stroke patients. The study was a longitudinal prospective study, conducted from June to October 2017, sampling was done three times day 1,3,7. Nitric oxide and absolute neutrophil count were examined. NO examination using Chemwell Analyzer and Absolute neutrophil count using SYSMEX XN-1000. 21 patients participated in the study (14 males (66.67%), 7 females (33.33%), Anova test had no difference in absolute neutrophil counts on day 1,3,7 (p = 0,001) and kruskall test. There was no difference between the levels of Nitric oxide days 1,3,7 (p = 0.716). Spearman's correlation test results there were no relation between absolute neutrophil count and outcomes in acute ischemic stroke (p = 0.001) and no nitric oxide relationship with outcome (p > 0.05). The absolute neutrophil count can be an outcome in acute ischemic stroke patients, so it is recommended that the clinician observes the absolute neutrophil count and can be used as a prognosis in acute ischemic stroke patients and to perform more specific nitric oxide examinations (eNOS, nNOS, iNOS) in ischemic stroke patients